Insidensi Nematoda Gastrointestinal dan Protozoa pada Monyet Ekor Panjang (Macaca fascicularis) Liar di Taman Wisata Alam (TWA) Pulau Weh Sabang - Rahmi, Erdiansyah; Hanafiah, Muhammad; Sutriana, Amalia; Hambal, Muhammad; Wajidi, Farid (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2010)
The research aims to find out the  incidence of gastrointestinal parasite in wild long tail macaque in wildlife  reserve  park, Weh  Island, Sabang. For  that purpose,  fecal  specimens  from 25 wild  long  tail macaques  in Weh  Island-  Sabang were  collected.  The  fresh  faeces  samples were  then  preserved  using AFA  (alcohol-formal-acetic)  liquid  prior  to  be  examined  in  Parasitology  Laboratorium,  Faculty  of Veterinary Medicine, Syiah Kuala University.   The  presence of gastrointestinal  parasite was  observed using centrifuge method as well as Boray  sedimentation method. The obtained data were tabulated and analyzed  descriptively.  The  result  revealed  that  two  parasite  species  were  found  in  gastrointestine; Eimeria  spp.    (12%)  and  Strongloides  spp.  (8%).  It  could  be  concluded  that  the  prevalence  of gastrointestinal  parasite  in wild  long  tail macaque  in wildlife  reserve  park, Weh  Island-  Sabang was considered mild.